PC / ASA alloy material, preparation method and application thereof
Patent Information
- Application Number
- CN202511779073.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-28
- Publication Date
- 2026-09-08
- Estimated Expiration
- 2045-11-28
AI Technical Summary
[0003]然而,传统PC/ASA材料面临以下挑战(1)环保压力:原生塑料的碳足迹高,需提高再生料(rPC/rASA)比例以满足可持续发展需求;(2)再生料性能劣化:再生料由于多次加工导致分子链断裂、端基氧化等问题,影响合金力学性能、光泽度和耐候性
[0050] (1) The present invention mixes recycled PC resin into PC/ASA alloy material and adopts a specific compatibilizer system and light stabilizer system to overcome the performance degradation caused by the use of recycled materials, realize the efficient utilization of recycled materials, and the obtained PC/ASA alloy material has excellent gloss, mechanical properties and weather resistance.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of polymer materials, and in particular to a PC / ASA alloy material, its preparation method, and its applications. Background Technology
[0002] PC / ASA alloys, formed from graft copolymers of polycarbonate (PC) and acrylate rubbers with acrylonitrile and styrene (ASA), possess excellent mechanical and thermal properties and are widely used in automotive, home appliance, and electronic materials industries. With the development of automotive and electronic materials, high-gloss, paint-free, environmentally friendly materials are becoming a trend. Surface gloss has become an important performance indicator for plastic products, and the development of high-gloss PC / ASA alloys as enclosure materials for electronic and electrical appliances is gaining increasing recognition from manufacturers.
[0003] However, traditional PC / ASA materials face the following challenges: (1) Environmental pressure: Virgin plastics have a high carbon footprint, and the proportion of recycled materials (rPC / rASA) needs to be increased to meet the needs of sustainable development; (2) Deterioration of recycled material performance: Due to multiple processing, recycled materials have problems such as molecular chain breakage and end group oxidation, which affect the mechanical properties, gloss and weather resistance of the alloy; (3) Requirements for high gloss without spraying: Traditional high gloss materials rely on spraying or UV coating, which is costly and not environmentally friendly, and there is an urgent need for a spray-free solution for direct injection molding. CN119505508A discloses a high gloss spray-free recycled PC / ASA alloy material and its preparation method and application. By adding compatibilizer and silicone powder to the raw materials of PC / ASA alloy material, the alloy material obtained has excellent scratch resistance, but the mechanical properties of the alloy still need to be further improved, and the weather resistance of the alloy material prepared is not mentioned.
[0004] Therefore, existing technologies still suffer from insufficient mechanical properties and weather resistance of alloys containing recycled materials. How to efficiently utilize recycled materials and overcome the performance degradation caused by their use is an urgent problem to be solved. Summary of the Invention
[0005] To address the aforementioned technical problems, this invention provides a PC / ASA alloy material, its preparation method, and its application. By incorporating recycled PC resin into the raw materials of the PC / ASA alloy material and employing a specific compatibilizer system and light stabilizer system, the performance degradation caused by the use of recycled materials is overcome, achieving efficient utilization of recycled materials. Furthermore, the resulting PC / ASA alloy material exhibits excellent gloss, mechanical properties, and weather resistance.
[0006] To achieve this objective, the present invention adopts the following technical solution:
[0007] In a first aspect, the present invention provides a PC / ASA alloy material, wherein the PC / ASA alloy material comprises the following components by weight: 30-70 parts of PC resin, 10-40 parts of recycled PC resin, 5-20 parts of ASA resin, 1-5 parts of compatibilizer A, 2-10 parts of compatibilizer B, and 0.5-2 parts of light stabilizer.
[0008] The compatibilizer A includes epoxy compatibilizers;
[0009] The compatibilizer B includes a compatibilizer containing disulfide bonds.
[0010] The PC resin can be, for example, 30 parts, 40 parts, 50 parts, 60 parts, or 70 parts; the recycled PC resin can be, for example, 10 parts, 20 parts, 30 parts, or 40 parts; the ASA resin can be, for example, 5 parts, 10 parts, 15 parts, or 20 parts; the compatibilizer A can be, for example, 1 part, 2 parts, 3 parts, 4 parts, or 5 parts; the compatibilizer B can be, for example, 2 parts, 4 parts, 6 parts, 8 parts, or 10 parts; and the light stabilizer can be, for example, 0.5 parts, 1 part, 1.5 parts, or 2 parts.
[0011] On the one hand, this invention introduces recycled PC resin into the PC / ASA alloy system to replace a portion of the non-recycled PC resin, and uses a specific compatibilizer system to overcome the problem of a significant decrease in alloy performance caused by the use of recycled materials, thus achieving efficient utilization of recycled materials. Specifically, the epoxy groups in the epoxy compatibilizer can react with the end groups (hydroxyl or carboxyl groups) in the PC / ASA alloy material, improving the weather resistance and mechanical properties of the PC / ASA alloy material. The compatibilizer containing disulfide bonds introduces disulfide groups with dynamic covalent bonds into the PC / ASA alloy material, forming a reversible cross-linking network with the resin matrix, thus improving the interfacial compatibility between recycled and non-recycled materials. On the other hand, this invention also improves the weather resistance of the PC / ASA alloy material by adding a light stabilizer.
[0012] This invention employs a synergistic compounding system of epoxy compatibilizers and disulfide bond-containing compatibilizers. The epoxy compatibilizers, with their high ring strain ternary epoxy rings, can establish a robust phase interface with the resin matrix through strong covalent bonds. The disulfide bond-containing compatibilizers optimize the processing through reversible bonding and endow the alloy materials with self-healing / reprocessing capabilities, greatly promoting the diffusion and positioning of compatibilizer molecules at the interface, resulting in a more uniform and robust interface layer. The compounding system forms an interpenetrating interface structure where "epoxy bridging points" are surrounded and supported by a "dynamic network of disulfide bonds." This structure is both strong and tough, far exceeding the effects achievable with a single compatibilizer. If epoxy compatibilizers are used alone, the resulting phase interfaces are all rigid and irreversible covalent bonds. When the alloy material is subjected to impact, the stress cannot be effectively dissipated through bond breakage and recombination, which easily leads to brittle fracture at the interface and poor impact resistance. Moreover, once the reaction is completed during processing, it cannot be reversed. If the processing technology is not properly controlled, it may lead to problems such as gelation or poor flowability. If compatibilizers containing disulfide bonds are used alone, since disulfide bonds are dynamically reversible, the interfaces constructed by them may undergo creep or relaxation at room temperature or under stress. The long-term dimensional stability, creep resistance, and modulus of the alloy material are usually poor, making it difficult to meet the requirements of structural materials.
[0013] Preferably, the amount of epoxy compatibilizer in the PC / ASA alloy material is less than the amount of compatibilizer containing disulfide bonds.
[0014] In this invention, if there is too much epoxy compatibilizer, it will lead to excessive cross-linking of the system, poor fluidity, and thus affect the overall performance of the alloy material.
[0015] Preferably, the amount of recycled PC resin in the PC / ASA alloy material is less than the amount of PC resin used.
[0016] The recycled PC resin used in this invention is 100% recycled PC, and its sources include, but are not limited to, recycled PC materials such as water buckets, car lights, and decorative strips.
[0017] Preferably, the epoxy compatibilizer comprises any one or a combination of at least two of styrene-acrylonitrile-glycidyl methacrylate, phenyl glycidyl ether, bisphenol A bisglycidyl ether, or tetra(phenylglycidyl ether) ethane.
[0018] Preferably, the compatibilizer containing disulfide bonds includes any one or a combination of at least two of the following: polyether compounds containing disulfide blocks, carboxylic acid compounds containing disulfide bonds, or zinc carboxylate salt compounds containing disulfide bonds.
[0019] Preferably, the polyether compound containing disulfide blocks includes polyethylene glycol containing dithiodipropionic acid blocks.
[0020] Preferably, the carboxylic acid compound containing a disulfide bond includes 2,2'-dithiodibenzoic acid.
[0021] Preferably, the zinc carboxylate salt compound containing disulfide bonds includes 1-vinyl-3-ethylimidazolium dithiocarboxylate zinc salt.
[0022] Preferably, the compatibilizer containing disulfide bonds comprises a composition of polyethylene glycol containing dithiodipropionic acid blocks, 2,2'-dithiodibenzoic acid, and zinc salt of 1-vinyl-3-ethylimidazolium dithiocarboxylate.
[0023] In the compatibilizer compound system containing disulfide bonds provided by this invention, the zinc carboxylate salt compound containing disulfide bonds and the carboxylic acid compound containing disulfide bonds have the advantages of fast reaction speed and high initial stability efficiency. They can effectively inhibit the early thermo-oxidative degradation of alloy materials in high-temperature and high-shear processes such as mixing and extrusion, thereby protecting the molecular chain structure from the source and endowing the alloy materials with better long-term performance. Meanwhile, the polyether compound containing disulfide block has the advantages of strong complexing ability and no catalytic risk. It can neutralize the harmful byproduct ZnCl2 produced by the reaction of zinc carboxylate salt and inhibit "zinc combustion", so that the stabilizing effect can be maintained for a long time. The resulting alloy material can maintain good color and performance throughout the entire processing cycle.
[0024] In the compound system of compatibilizers containing disulfide bonds provided by the present invention, if any one of them is used alone or in excessive amounts, the compatibilizer containing disulfide bonds will have a poor binding effect with the system. Instead, as a small molecule, it will degrade during the subsequent extrusion molding process and will be difficult to form a homogeneous structure in the alloy material.
[0025] Preferably, the polyether compound containing disulfide blocks accounts for 1-10% of the total mass of the compatibilizer containing disulfide bonds, for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc.
[0026] Preferably, the light stabilizer includes light stabilizer A and / or light stabilizer B.
[0027] Preferably, the light stabilizer A comprises a γ-methacryloxypropyltrimethoxysilane-modified hydroxyphenyltriazine UV absorber.
[0028] Preferably, the light stabilizer B includes benzotriazole light stabilizers and / or hindered amine light stabilizers.
[0029] The light stabilizer B used in this invention can be selected from commercially available benzotriazole light stabilizers and / or commercially available hindered amine light stabilizers.
[0030] Preferably, the mass ratio of light stabilizer A to light stabilizer B in the light stabilizer is 1:(1-15), for example, it can be 1:1, 1:2, 1:5, 1:8, 1:10, 1:13 or 1:15, etc.
[0031] This invention employs a novel light stabilizer compound system, comprising a γ-methacryloxypropyltrimethoxysilane-modified hydroxyphenyltriazine UV absorber and a conventional commercially available light stabilizer. In this system, only a small amount of the γ-methacryloxypropyltrimethoxysilane-modified hydroxyphenyltriazine UV absorber needs to be added in combination with the conventional commercially available light stabilizer to significantly improve the weather resistance of PC / ASA alloy materials. However, if too much of the γ-methacryloxypropyltrimethoxysilane-modified hydroxyphenyltriazine UV absorber is added, stress concentration points will form, thereby affecting the overall mechanical properties of the alloy material.
[0032] Preferably, the PC / ASA alloy material further comprises, by weight, any one or a combination of at least two of the following: 0.01-0.15 parts chain extender, 1-10 parts toughening agent, 0.5-3 parts hydrolysis inhibitor, 0.5-3 parts lubricant, 0.1-0.5 parts antioxidant, 0.005-0.02 parts carbon black, or 0.0001-0.001 parts pigment.
[0033] Among them, 0.01-0.15 portions can be, for example, 0.01 portions, 0.02 portions, 0.04 portions, 0.06 portions, 0.08 portions, 0.1 portions, 0.12 portions, 0.14 portions, or 0.15 portions, etc.; 1-10 portions can be, for example, 1 portion, 2 portions, 4 portions, 6 portions, 8 portions, or 10 portions, etc.; 0.5-3 portions can be, for example, 0.5 portions, 1 portion, 1.5 portions, 2 portions, 2.5 portions, or 3 portions, etc.; 0.1-0.5 For example, a portion can be 0.1, 0.2, 0.3, 0.4, or 0.5 portions; 0.005-0.02 portions can be 0.005, 0.01, 0.015, or 0.02 portions; 0.0001-0.001 portions can be 0.0001, 0.0002, 0.0004, 0.0005, 0.0006, 0.0008, or 0.001 portions.
[0034] Preferably, the chain extender comprises polycarbodiimide.
[0035] Preferably, the toughening agent comprises MBS.
[0036] Preferably, the hydrolysis inhibitor comprises aromatic polycarbodiimide.
[0037] Preferably, the lubricant comprises any one or a combination of at least two of stearic acid, polyolefin wax, microcrystalline wax, oleamide, calcium stearate, zinc stearate, magnesium stearate, or butyl stearate.
[0038] Preferably, the antioxidant comprises any one or a combination of at least two of hindered phenolic antioxidants, thioester antioxidants, phosphite antioxidants, or hindered amine antioxidants.
[0039] The carbon black and pigments used in this invention can be selected from commercially available carbon black and pigments.
[0040] In a second aspect, the present invention provides a method for preparing PC / ASA alloy material as described in the first aspect, the method comprising the following steps: mixing the raw material components of PC / ASA alloy material, and then performing melt granulation to obtain the PC / ASA alloy material.
[0041] Preferably, the mixing time is 1-30 min, for example, it can be 1 min, 10 min, 20 min, or 30 min.
[0042] Preferably, the melt granulation involves feeding the mixed material into a twin-screw extruder, and then extruding, cooling, drying, and pelletizing it to obtain the PC / ASA alloy material.
[0043] Preferably, the temperatures of each zone of the twin-screw extruder are as follows: Zone 1: 225-235℃; Zone 2: 235-245℃; Zone 3: 245-255℃; Zone 4: 260-270℃; Zone 5: 260-270℃; Zone 6: 260-270℃; Zone 7: 260-270℃; Zone 8: 255-265℃; Zone 9: 255-265℃; Zone 10: 255-265℃; Zone 11: 255-265℃.
[0044] Among them, 225-235℃ can be, for example, 225℃, 226℃, 228℃, 230℃, 232℃, 234℃ or 235℃; 235-245℃ can be, for example, 235℃, 236℃, 238℃, 240℃, 242℃, 244℃ or 245℃; 245-255℃ can be, for example, 245℃, 246℃, 248℃, 250℃, 252℃, 254℃ or 255℃; 260-270℃ can be, for example, 260℃, 262℃, 264℃, 265℃, 266℃, 268℃ or 270℃; 255-265℃ can be, for example, 255℃, 256℃, 258℃, 260℃, 262℃, 264℃ or 265℃.
[0045] Preferably, the screw speed of the twin-screw extruder is 500-800 r / min, for example, it can be 500 r / min, 550 r / min, 600 r / min, 650 r / min, 700 r / min, 750 r / min or 800 r / min.
[0046] Preferably, the residence time of the mixture in the twin-screw extruder is 3-5 min, for example, 3 min, 3.5 min, 4 min, 4.5 min or 5 min.
[0047] When the raw materials for preparing the PC / ASA alloy material provided by this invention contain carbon black and pigment, the preparation method is as follows: First, the remaining raw materials except for carbon black and pigment are mixed for a mixing time of 1-10 min, for example, 1 min, 2 min, 4 min, 5 min, 6 min, 8 min or 10 min, to obtain a premix. Then, carbon black and pigment are mixed with the premix for a mixing time of 10-20 min, for example, 10 min, 12 min, 14 min, 15 min, 16 min, 18 min or 20 min, and then the obtained mixture is melt-granulated to obtain the PC / ASA alloy material.
[0048] Thirdly, the present invention provides an application of the PC / ASA alloy material as described in the first aspect in the fields of automobiles, communication equipment, or electronic appliances.
[0049] Compared with the prior art, the present invention has at least the following beneficial effects:
[0050] (1) The present invention mixes recycled PC resin into PC / ASA alloy material and adopts a specific compatibilizer system and light stabilizer system to overcome the performance degradation caused by the use of recycled materials, realize the efficient utilization of recycled materials, and the obtained PC / ASA alloy material has excellent gloss, mechanical properties and weather resistance.
[0051] (2) Specifically, the PC / ASA alloy material provided by the present invention has a tensile strength of up to 49-55 MPa, a flexural modulus of up to 1870-2100 MPa, and a notched impact strength of up to 21-57 kJ / m. 2 The Vicat softening point temperature is 129-137℃, the gloss at 20° can reach 75-105, and the gray level is greater than 3. Detailed Implementation
[0052] To facilitate understanding of the present invention, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of the invention.
[0053] The specific information of the materials used in the following specific embodiments of the present invention is as follows:
[0054] PC resin, bisphenol A type polycarbonate, weight average molecular weight of 15000-40000 g / mol, purchased from Makrolon® 2407;
[0055] Recycled PC resin, PC-08, purchased from Guangzhou Boshan New Materials Co., Ltd.
[0056] ASA resin, with a weight-average molecular weight of 15,000-25,000 g / mol, was purchased from INEOS Styrenex, Luran S® 757G;
[0057] Compatibilizer A, styrene-acrylonitrile-glycidyl methacrylate (SAG), with an epoxy group content of 6-10%, was purchased from Nantong Rizhisheng New Technology Development Co., Ltd.
[0058] Compatibilizer B, polyethylene glycol containing dithiodipropionic acid blocks, with a number average molecular weight of 800-5000 g / mol, was purchased from Sigma-Aldrich.
[0059] Compatibilizer B, 2,2'-dithiodibenzoic acid;
[0060] Compatibilizer B, zinc salt of 1-vinyl-3-ethylimidazolium dithiocarboxylate;
[0061] Light stabilizer A, γ-methacryloxypropyltrimethoxysilane modified hydroxyphenyltriazine UV absorber.
[0062] The γ-methacryloxypropyltrimethoxysilane-modified hydroxyphenyltriazine UV absorber was prepared by the following method:
[0063] Cyanuric chloride and resorcinol were mixed at a mass ratio of 1:1.5, reacted at 0°C for 1.5 h, and then reacted at 45°C for 5 h to obtain 2,4-bis(2',4'-dihydroxyphenyl)-6-phenyl-1,3,5-triazine intermediate;
[0064] The 2,4-bis(2',4'-dihydroxyphenyl)-6-phenyl-1,3,5-triazine intermediate was then mixed with KH-570, potassium carbonate, and DMF. The mass ratio of the 2,4-bis(2',4'-dihydroxyphenyl)-6-phenyl-1,3,5-triazine intermediate, KH-570, and potassium carbonate was 1:1:2.5. The mixture was then reacted under nitrogen at 80°C for 7 h to obtain the γ-methpropyleneoxypropyltrimethoxysilane-modified hydroxyphenyltriazine UV absorber.
[0065] Light stabilizer B, UV-327;
[0066] Light stabilizer B, GW-944Z;
[0067] Chain extender, polycarbodiimide A298745, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., molecular weight 4000, analytical grade, purity ≥95%;
[0068] Toughening agent, MBS, purchased from Dow Chemical, USA, BTA-731;
[0069] Hydrolysis inhibitor, diimine-type hydrolysis inhibitor, A298745, number average molecular weight 3000-7000, purity ≥95%;
[0070] Lubricant, Plasticizer DPHP, purchased from BASF;
[0071] Antioxidant, IRGANOX 1076, purchased from BASF;
[0072] Carbon black, purchased from Cabot;
[0073] Pigment, Macrolex Red 5B, purchased from Farbtex / Lanxess.
[0074] Examples 1-11, Comparative Examples 1-4
[0075] Examples 1-11 and Comparative Examples 1-4 respectively provide a PC / ASA alloy material and its preparation method. The raw materials and their proportions for preparing the PC / ASA alloy material are shown in Tables 1-2 (the amounts of each component in Tables 1-2 are all by weight), where "--" indicates that the component was not added; the preparation method of the PC / ASA alloy material is as follows:
[0076] (1) According to the formula, PC resin, ASA resin, recycled PC resin, SAG, polyethylene glycol containing dithiodipropionic acid block, 2,2'-dithiodibenzoic acid, 1-vinyl-3-ethylimidazolium dithiocarboxylate zinc salt, γ-methpropyleneoxypropyltrimethoxysilane modified hydroxyphenyltriazine UV absorber, UV-327, GW-944Z, polycarbodiimide, MBS, A298745, Plasticizer DPHP, and IRGANOX 1076 are mixed for the first time in a high-speed mixer at a speed of 500 rpm for 5 min. After the first mixing, carbon black and Macrolex Red 5B are added for the second mixing at a speed of 1000 rpm for 15 min to obtain the mixture.
[0077] (2) The mixture obtained in step (1) is added to a twin-screw extruder for melt co-extrusion. The extruder temperatures are: Zone 1: 230℃, Zone 2: 240℃, Zone 3: 250℃, Zone 4: 265℃, Zone 5: 265℃, Zone 6: 265℃, Zone 7: 265℃, Zone 8: 260℃, Zone 9: 260℃, Zone 10: 260℃, Zone 11: 260℃. The extruder screw speed is 600 r / min, and the residence time is 3 min. After extrusion by the screw, the mixture is cooled, dried, and pelletized to obtain PC / ASA alloy material.
[0078] Table 1
[0079]
[0080] Table 2
[0081]
[0082] The properties of the PC / ASA alloy materials provided in the above embodiments and comparative examples were characterized using the following specific test methods:
[0083] Tensile strength (MPa): Tested according to ISO 527, at a speed of 50 mm / min and a temperature of 23℃.
[0084] Flexural modulus (MPa): Tested according to ISO 178, with a test speed of 2 mm / min and a span of 64 mm.
[0085] Notched impact strength (kJ / m) 2 ): The test was conducted according to the test method of ISO 179-1, and the test temperature was 23℃;
[0086] Vicat softening point temperature (°C): Tested according to the test method of GB / T 1633-2000;
[0087] 20° gloss: Measured using a German BYK gloss meter;
[0088] Gray level: The test is conducted in accordance with the test method of "PV1303 5P0". The higher the gray level, the smaller the color change and the better the aging resistance of the material.
[0089] Test Results
[0090] The PC / ASA alloy materials provided in Examples 1-9 and Comparative Examples 1-4 were tested according to the above test methods. The test data are shown in Table 3.
[0091] Table 3
[0092]
[0093] The test results show that:
[0094] (1) As can be seen from Examples 1 to 9, the present invention incorporates recycled PC resin into PC / ASA alloy materials and uses a specific compatibilizer system and light stabilizer system to overcome the performance degradation caused by the use of recycled materials, thereby achieving efficient utilization of recycled materials. The resulting PC / ASA alloy materials have excellent gloss, mechanical properties and weather resistance, with tensile strength reaching 49-55 MPa, flexural modulus reaching 1870-2100 MPa and notched impact strength reaching 21-57 kJ / m. 2 The Vicat softening point temperature is 129-137℃, the gloss at 20° can reach 75-105, and the gray level is greater than 3.
[0095] (2) As can be seen from Examples 1 and 3-4, when the present invention is used in combination with benzotriazole light stabilizers and hindered amine light stabilizers, higher gloss and aging resistance can be obtained.
[0096] (3) As can be seen from Examples 1 and 5-7, when the present invention is used in combination with light stabilizer A and light stabilizer B, and only a small amount of γ-methacryloxypropyltrimethoxysilane modified hydroxyphenyltriazine UV absorber is added to compound with conventional commercially available light stabilizers, the weather resistance of PC / ASA alloy materials can be greatly improved. However, if too much γ-methacryloxypropyltrimethoxysilane modified hydroxyphenyltriazine UV absorber is added, stress concentration points will be formed, thereby affecting the overall mechanical properties.
[0097] (4) As can be seen from Examples 1 and 8-9 and Comparative Examples 2-3, the present invention uses a specific compatibilizer compound system to overcome the significant decline in alloy performance caused by the use of recycled materials, and achieves efficient utilization of recycled materials. However, using epoxy compatibilizers or compatibilizers containing disulfide bonds alone cannot achieve the technical effect of synergistic "enhancement and toughening" at the same time. Using one of the compatibilizers containing disulfide bonds alone will affect the appearance of the alloy material.
[0098] (5) As can be seen from Example 1 and Comparative Example 1, the addition of ASA to the PC / ASA alloy material formulation provided by the present invention can significantly improve the mechanical properties of PC, such as impact strength, so that the alloy material shows a good synergistic effect in terms of mechanical properties.
[0099] (6) As can be seen from Example 1 and Comparative Example 4, by limiting the amount of recycled PC added, under the PC / ASA alloy material formulation provided by the present invention, if the amount of recycled PC added is further increased, it will have a greater impact on the overall performance of the alloy material.
[0100] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. A PC / ASA alloy material, characterized in that, The PC / ASA alloy material comprises the following components by weight: 30-70 parts PC resin, 10-40 parts recycled PC resin, 5-20 parts ASA resin, 1-5 parts compatibilizer A, 2-10 parts compatibilizer B, and 0.5-2 parts light stabilizer. The compatibilizer A includes epoxy compatibilizers; The compatibilizer B includes a compatibilizer containing disulfide bonds; The epoxy compatibilizer includes any one or a combination of at least two of the following: styrene-acrylonitrile-glycidyl methacrylate, phenyl glycidyl ether, bisphenol A bisglycidyl ether, or tetra(phenylglycidyl ether) ethane. The compatibilizer containing disulfide bonds is a composition of polyethylene glycol containing dithiodipropionic acid blocks, 2,2'-dithiodibenzoic acid and zinc salt of 1-vinyl-3-ethylimidazolium dithiocarboxylate. The compatibilizer containing disulfide bonds is polyethylene glycol containing dithiodipropionic acid blocks, accounting for 1-10% of the total mass of the compatibilizer containing disulfide bonds.
2. The PC / ASA alloy material according to claim 1, characterized in that, The light stabilizer includes light stabilizer A and / or light stabilizer B; The light stabilizer A includes a γ-methacryloxypropyltrimethoxysilane-modified hydroxyphenyltriazine UV absorber; The light stabilizer B includes benzotriazole light stabilizers and / or hindered amine light stabilizers.
3. The PC / ASA alloy material according to claim 2, characterized in that, The mass ratio of light stabilizer A to light stabilizer B in the light stabilizer is 1:(1-15).
4. The PC / ASA alloy material according to claim 1, characterized in that, The PC / ASA alloy material further includes, by weight, any one or a combination of at least two of the following: 0.01-0.15 parts chain extender, 1-10 parts toughening agent, 0.5-3 parts hydrolysis inhibitor, 0.5-3 parts lubricant, 0.1-0.5 parts antioxidant, or 0.0001-0.001 parts pigment.
5. The PC / ASA alloy material according to claim 4, characterized in that, The chain extender includes polycarbodiimide; The toughening agent includes MBS; The hydrolysis inhibitor includes aromatic polycarbodiimide; The lubricant includes any one or a combination of at least two of stearic acid, polyolefin wax, microcrystalline wax, oleamide, calcium stearate, zinc stearate, magnesium stearate, or butyl stearate. The antioxidants include any one or a combination of at least two of the following: hindered phenolic antioxidants, thioester antioxidants, phosphite antioxidants, or hindered amine antioxidants.
6. A method for preparing the PC / ASA alloy material as described in any one of claims 1-5, characterized in that, The preparation method includes the following steps: mixing the raw material components of the PC / ASA alloy material, and then melting and granulating them to obtain the PC / ASA alloy material.
7. The preparation method according to claim 6, characterized in that, The mixing time is 1-30 min; The melt granulation process involves feeding the mixed material into a twin-screw extruder, where it is extruded, cooled, dried, and pelletized to obtain the PC / ASA alloy material.
8. The preparation method according to claim 7, characterized in that, The temperatures of each zone of the twin-screw extruder are as follows: Zone 1: 225-235℃; Zone 2: 235-245℃; Zone 3: 245-255℃; Zone 4: 260-270℃; Zone 5: 260-270℃; Zone 6: 260-270℃; Zone 7: 260-270℃; Zone 8: 255-265℃; Zone 9: 255-265℃; Zone 10: 255-265℃; Zone 11: 255-265℃. The screw speed of the twin-screw extruder is 500-800 r / min; The residence time of the mixture in the twin-screw extruder is 3-5 minutes.
9. The application of the PC / ASA alloy material according to any one of claims 1-5 in automotive housing materials, household appliance housing materials, and electronic and electrical appliance housing materials.
Citation Information
Patent Citations
High-weather-resistance PC / ASA alloy for automobile exterior decoration and preparation method of high-weather-resistance PC / ASA alloy
CN115785605A
High-gloss spraying-free reclaimed material PC / ASA alloy material as well as preparation method and application thereof
CN119505508A